ENGLISH COMMUNICATION SKILL: NEEDS AND NUTRITIONS FOR EMPOWERING THE TEACHER (International Journal of Food and Nutritional Sciences, 2022)
Learning styles and strategies differ from one to another. They are acquired only through practice and experience. The proper understanding and recognition of styles and strategies help us to improve the quality of learning. Learning styles are of different kinds. Environmental factors also determine the qualitative learning .School education is entirely different from college education. Teachers painstakingly explain, read out the text and ask questions to check understanding at schools. At college, the teacher no longer occupies the centre stage because lecture method is adopted. A learner ought to go beyond the lecture to purse learning. A learner adopts new learning skills and techniques for better understanding of his/her subject. Such learning styles and strategies make the students more active learners.